The Cerro Guanaco mass movements: A geophysical and morphometric approach on a megalandslide in the Fuegian Andes (Southern Patagonia). (August 2020) - Bran, Donaldo Mauricio; Lozano, Jorge Gabriel; Winocur, Diego; Menichetti, Marco; Onnis, Luciano; Lodolo, Emanuele; Tassone, Alejandro
Abstract: The Fuegian Andes, in the southernmost part of South America, are characterized by a relatively young deglacial landscape, where the glacial erosive relief is strongly influenced by regional-scale geological structures, resulting in deep longitudinal valleys with steeply dipping hillslopes. The rock-slope stability response to receding ice masses and the contribution of the gravitational processes in landscape evolution of the southernmost Andes, however, have not been assessed so far. The remoteness of the region, comprising a mountainous area hardly to access and piedmont and valley floors densely covered by forest, peatbogs or water bodies might partly explain the lack of such studies. Therefore, the objective of this contribution is to document for the first time the occurrence of massive slope failures in the Fuegian Andes using a multidisciplinary approach. This involves the use of indirect methods such as applied geophysics and landscape morphometrics. The southwest-facing slope of Cerro Guanaco, near Ushuaia, hosts several slope failures, but a massive failure stands out. The morphostructural approach allowed the geometrical description of the main dimensional characteristics of the first megalandslide recognized in the Fuegian Andes, which involved almost 1, 2 km 3 of material. On the other hand, the geophysical data has proved valuable in estimating the depth and characteristic of the buried detachment surface. The slope failure consisted of an initial translational movement followed by secondary slides and was developed shortly after the glacier recession. The gravitational processes represent an important element in the Fuegian deglacial landscape evolution. Highlights: Identification of large-scale landslides developed along metamorphic rocks of Cordon Guanaco. Geophysical and morphometric characterization of the 1.2 km 3 large Guanaco Megalandslide. Landslides are an important factor of deglacial landscape evolution in the Fuegian Andes. The slope failures are located near important waterbodies implying potential hazard.